AMPLITUDE, PHASE AND PATH ANOMALIES OF MANTLE WAVES - Woodhouse, J; Wong, Y (1986)
The amplitude and phase anomalies observed in long period Rayleigh and Love waves (T >150s) show definite patterns of variation from orbit to orbit. In some cases the phase anomalies agree with the prediction of linear perturbation theory applied to a spherical reference model (Fermat's Principle), namely that each complete orbit of the earth in either direction corresponds to a constant phase anomaly increment. The corresponding approximation for amplitude anomaly is derived in this study. Evidence is presented for orbits which have paths deviating from the great circle by >1000 km. A technique is outlined for making use of such data to constrain lateral variations in Earth structure.-from Authors